2010
DOI: 10.1590/s1679-62252010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Novel sex-related characteristics of the longsnout seahorse Hippocampus reidi Ginsburg, 1933

Abstract: This paper presents novel sex-related characteristics in Hippocampus reidi, expressed as a prominent and pigmented keel (males only), and by a row of dorsolateral spots mostly (97.4%) found in males. While the keel was found even in the smallest males sampled, the dorsolateral spots appear to be associated with body size. Ex situ observations revealed that during courtship males highlighted both characters by turning pale their background body colour. Understanding such colour and behavioural patterns is relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some monogamous species also use displays during pair bonding (e.g. Hippichthys penicillus, Watanabe et al ., ; Hippocampus reidi , Oliveira et al ., ), and in Corythoichthys haematopterus, the males possess a condition‐dependent ornament used in partner recognition (Matsumoto et al ., ; Sogabe, ). The Gulf pipefish ornaments are highlighted during courtship and female–female displays (Partridge et al ., ), but the type of signal the female ornament portrays is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some monogamous species also use displays during pair bonding (e.g. Hippichthys penicillus, Watanabe et al ., ; Hippocampus reidi , Oliveira et al ., ), and in Corythoichthys haematopterus, the males possess a condition‐dependent ornament used in partner recognition (Matsumoto et al ., ; Sogabe, ). The Gulf pipefish ornaments are highlighted during courtship and female–female displays (Partridge et al ., ), but the type of signal the female ornament portrays is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Females have a larger home range than males 9 and that increases probability of using holdfasts with an appropriate shape for grasping during displacement better than protection or feeding. Other studies have also documented this for H. reidi, 23,24,25 while Golani and Fine 26 and Teske et al 27 also reported marine debris and man-made holdfast use by H. fuscus and H. capensis Boulenger 1900, respectively. Hippocampus comes Cantor 1850 has been reported using pieces of wood and submerged cables, 14 and H. reidi has been noted as grasping pieces of wood.…”
Section: Discussionmentioning
confidence: 79%
“…Seahorses tend to be monogamous, and monogamy seems to be reinforced by daily greetings, as reported for H. whitei, 19 H. fuscus, 20 H. zosterae 21 and H. reidi. 23 Therefore, selecting the same habitat would reduce effort and energy waste in finding a partner.…”
Section: Discussionmentioning
confidence: 99%
“…The RFE is located in the Guadalupe Environmental Protection Area ( Área de Proteção Ambiental de Guadalupe—APAG ), created with the objective of mitigating socio-environmental conflicts, which mostly involve disordered tourism, predatory fishing, shrimp farming, and agricultural (sugar cane) pollution ( Santos, 2002 ; Araújo, Alves & Simões, 2014 ). Previous studies have recorded the occurrence of H. reidi in the Rio Formoso Estuary ( Rosa et al, 2007 ; Oliveira, Castro & Rosa, 2010 ; Aylesworth et al, 2015 ), and recently a decline of 60–90% of the seahorse population in the Ariquindá River has been verified (TPR Oliveira, 2019, unpublished data).…”
Section: Methodsmentioning
confidence: 95%
“…The species is distributed from Cape Hatteras, United States, to the Gulf of Mexico and Brazil ( Lourie, Pollom & Foster, 2016 ). Its occurrence is reported along all the Brazilian coast, from the northern state of Pará to the southern state of Rio Grande do Sul ( Rosa, 2005 ; Chao et al, 1982 ), and can be found in shallow reefs, rocky shores, and seagrass beds ( Dias-Neto, 2011 ; Rosa et al, 2005 ; Rosa et al, 2007 ; Oliveira, Castro & Rosa, 2010 ; Freret-Meurer et al, 2018 ). However, H. reidi occurrence has been mostly reported in mangrove estuaries on the NE coast ( Rosa et al, 2007 ), using structures such as mangrove roots, fallen branches, macroalgae, and sponges as micro-habitats ( Dias & Rosa, 2003 ; Rosa et al, 2005 ; Rosa et al, 2007 ; Mai & Rosa, 2009 ).…”
Section: Introductionmentioning
confidence: 99%